Policies for Improved Food Security: - The Roles of Land Tenure Policies and Land Markets - Stein T Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2017)
This chapter provides an overview of what we know about farm size distributions, the emerging land markets, the role of tenure systems, tenure reforms and land policies in shaping the distribution of increasingly scarce land resources. The primary focus is on Africa while making some comparisons with Asia. Climate risk and change have serious implications for household vulnerability and food security. While there is a need to absorb further population growth in rural areas, a rapid rise in rural-urban migration is inevitable. Careful land use planning and tenure reforms are needed to smooth the transition towards more intensive land use.
Keywords: Q15; 330; Small farms; food security; land tenure; land markets; land governance